An indie hype cycle built for two: a case study of the Pitchfork album reviews of Arcade Fire and Clap Your Hands Say Yeah - Ernst, Samuel R., author; Lupo, Jonathan, advisor; Diffrient, David Scott, committee member; Thompson, Deborah, committee member (Colorado State University. Libraries, 2012)
This thesis investigates the whims of critical reception in the indie rock world and its effects upon the hype cycle. I define the indie hype cycle as a naturalized communicative process governing the flow of critical favor within the indie music community and identify its four primary phases as entrance on to the scene, hype generation, backlash, and obscurity/visibility. To understand the interaction between the hype cycle and critical reception, the project focuses on Arcade Fire and Clap Your Hands Say Yeah (CYHSY) as two bands emblematic of the critical divergence possible after initial success. It compares the reviews of the bands' debut and sophomore albums by Pitchfork, a prominent indie music website, and identifies genre, elitism, and authenticity as key constructs in the way the site frames the bands as indie, and thus, worthy of praise. I argue that an economy of authenticity--featuring emotional, economic, and talent-based forms--affects the indie hype cycle in a variety of ways. The thesis concludes that the mechanics of indie music criticism have extensive influence upon the indie hype cycle. The initial framing of band authenticity that accompanies debut releases can have years-long ramifications on the way that band is received and covered in the indie press. To inform its analysis, the thesis draws upon a wide variety of scholars including Ryan Hibbet, Michael Albrecht, and Devon Powers, along with commentators from the popular music press including Carl Wilson and Nitsuh Abebe.
Keywords: popular music; Arcade Fire; authenticity; hype cycle; indie; Pitchfork